Activin Receptor‐Like Kinase 4 Haplodeficiency Mitigates Arrhythmogenic Atrial Remodeling and Vulnerability to Atrial Fibrillation in Cardiac Pathological Hypertrophy. Issue 16 (21st August 2018) - Wang, Qian; Chen, Yihe; Zhang, Daoliang; Li, Changyi; Chen, Xiaoqing; Hou, Jianwen; Fei, Yudong; Wang, Yuepeng; Li, Yigang
Abstract : Background: Activin receptor‐like kinase 4 (ALK4) is highly expressed in mammal heart. Atrial fibrillation (AF) is closely related to ventricular pressure overload. Because pressure overload increases atrial pressure and leads to atrial remodeling, it would be informative to know whether ALK4 exerts potential effects on atrial remodeling and AF vulnerability in a pressure‐overload model. Methods and Results: Wild‐type littermates and ALK4 +/− mice were subjected to abdominal aortic constriction or a sham operation. After 4 or 8 weeks, echocardiographic and hemodynamic measurements were performed, and inducibility of AF was tested. The hearts were divided into atria and ventricles and then were fixed in formalin for staining, or they were weighted and snap‐frozen for quantitative real‐time polymerase chain reaction and Western blot analysis. Compared with wild‐type littermates, ALK4 +/− mice demonstrated a similar extent of atrial hypertrophy but significantly suppressed atrial fibrosis at 8 weeks post–abdominal aortic constriction. ALK4 haplodeficiency partially blocked abdominal aortic constriction–induced upregulation of monocyte chemotactic protein 1 and interleukin‐6, and the increased chemotaxin of macrophages. ALK4 haplodeficiency also blunted a reduction of connexin 40 and redistribution of connexin 43 from the intercalated disk to the lateral membranes, thereby improving localized conduction abnormalities. Meanwhile, ALK4 haplodeficiency inhibited abdominal aortic constriction–induced decreased IN a, IC a‐L and IK 1 densities as well as the accompanying action potential duration shortening. Mechanistically, ALK4 haploinsufficiency resulted in the suppression of Smad2/3 activity in this model. Conclusions: Our results demonstrate that ALK4 haplodeficiency ameliorates atrial remodeling and vulnerability to AF in a pressure‐overload model through inactivation of the Smad2/3 pathway, suggesting that ALK4 might be a potential therapeutic target in combating pressure overload–induced AF.